Desert Dust Outbreaks over Mediterranean Basin: A Modeling, Observational, and Synoptic Analysis Approach. (16th September 2012) - Calastrini, F.; Guarnieri, F.; Becagli, S.; Busillo, C.; Chiari, M.; Dayan, U.; Lucarelli, F.; Nava, S.; Pasqui, M.; Traversi, R.; Udisti, R.; Zipoli, G.
Abstract : Dust intrusions from African desert regions have an impact on the Mediterranean Basin (MB), as they cause an anomalous increase of aerosol concentrations in the tropospheric column and often an increase of particulate matter at the ground level. To estimate the Saharan dust contribution to PM10, a significant dust intrusion event that occurred in June 2006 is investigated, joining numerical simulations and specific measurements. As a first step, a synoptic analysis of this episode is performed. Such analysis, based only on meteorological and aerosol optical thickness observations, does not allow the assessment of exhaustive informations. In fact, it is not possible to distinguish dust outbreaks transported above the boundary layer without any impact at the ground level from those causing deposition. The approach proposed in this work applies an ad hoc model chain to describe emission, transport and deposition dynamics. Furthermore, physical and chemical analyses (PIXE analysis and ion chromatography) were used to measure the concentration of all soil-related elements to quantify the contribution of dust particles to PM10 . The comparison between simulation results and in-situ measurements show a satisfying agreement, and supports the effectiveness of the model chain to estimate the Saharan dust contribution at ground level.